2022
DOI: 10.12998/wjcc.v10.i31.11466
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of polymyxin-induced nephrotoxicity and its predictors in critically ill adult patients: A meta-analysis

Abstract: BACKGROUND Polymyxin-induced nephrotoxicity is a major safety concern in clinical practice due to long-term adverse outcomes and high mortality. AIM To conducted a systematic review and meta-analysis of the prevalence and potential predictors of polymyxin-induced nephrotoxicity in adult intensive care unit (ICU) patients. METHODS PubMed, EMBASE, the Cochrane Library and Reference Citation Analysis database were searched for relevant studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Studies have shown that nephrotoxicity is dose limiting for polymyxins [ 19 , 41 , 42 ]. Two recent meta-analyses showed that the overall incidences of CMS- and PMB-induced nephrotoxicity were 34.8% and 45%, respectively [ 43 , 44 ]. Compared with those of CMS and polymyxin B, the event of renal impairment associated with colistin sulfate was considerably lower (up to 9.2%) [ 21 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that nephrotoxicity is dose limiting for polymyxins [ 19 , 41 , 42 ]. Two recent meta-analyses showed that the overall incidences of CMS- and PMB-induced nephrotoxicity were 34.8% and 45%, respectively [ 43 , 44 ]. Compared with those of CMS and polymyxin B, the event of renal impairment associated with colistin sulfate was considerably lower (up to 9.2%) [ 21 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polymyxins are toxic drugs and are associated with many adverse events; renal toxicity is one of the most important. A recent meta-analysis showed that the prevalence of nephrotoxicity during polymyxin treatment in the ICU was 34.8%, similar to the non-ICU setting [ 29 ]. We should consider the balance between the potential benefit of liberally using empirical polymyxins and the risk of severe adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The observed 28-day or in-hospital all-cause mortality rates also varied from studies for colistin sulfate, with a wide range of 9.3%–44% ( Hao et al, 2022 ; Jin et al, 2022 ; Lu et al, 2022 ; Peng et al, 2023 ). However, compared with colistimethate sodium or polymyxin B sulfate, colistin sulfate is associated with less nephrotoxicity, as demonstrated in recent real-world studies ( Hao et al, 2022 ; Jin et al, 2022 ; Lu et al, 2022 ; Wang et al, 2022 ; Peng et al, 2023 ). These findings suggest the necessity for further evaluation of the mortality risk factors related to CRO infections during colistin sulfate treatment.…”
Section: Introductionmentioning
confidence: 85%